1970
DOI: 10.1099/00221287-63-2-141
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Esterases and Their Function in Candida lipolytica, Aspergillus niger and a Yeast-like Fungus

Abstract: S U M M A R YEsterases, determined by polyacrylamide gel electrophoresis, were present when Candida lipolytica was grown in a liquid, shaken, glucose-mineral salts medium. Intracellular esterase activity increased during growth, but extracellular esterase activity was small and increased only marginally. Esterases were not detected in organisms grown on solid glucose-mineral salts medium, but were present when glycerol tributyrin replaced glucose.At the onset of asexual sporulation in a yeast-like fungus, thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1972
1972
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Lipases from yeasts are gaining industrial interest with applications in laundry detergents and in dairy industries (Burden and Eveleight 1990), while little attention has so far been paid to esterases from yeasts (Lloyd et al 1971;Basaran and Hang 2000). Apparently, in the present study, the occurrence of EsA was essentially associated with basidiomycetes, while the occurrence of LipA was associated with ascomycetes (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Lipases from yeasts are gaining industrial interest with applications in laundry detergents and in dairy industries (Burden and Eveleight 1990), while little attention has so far been paid to esterases from yeasts (Lloyd et al 1971;Basaran and Hang 2000). Apparently, in the present study, the occurrence of EsA was essentially associated with basidiomycetes, while the occurrence of LipA was associated with ascomycetes (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 46%
“…Lipases from yeasts are gaining industrial interest with applications in laundry detergents and in dairy industries (Burden and Eveleight 1990), while little attention has so far been paid to esterases from yeasts (Lloyd et al . 1971; Basaran and Hang 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the microbial esterases are usually considered as inducible enzymes, their production being promoted by their substrates (Donaghy and Mckay 1992;Isobe and Wakao 1996;Lloyd et al 1971). When Tween 80 was omitted from the growth medium, the lipolytic activity from strain DF-E4 could still be detected from fractions E, I and M, indicating that the extracellular esterase is constitutively produced irrespective of the presence of inducer (Tween 80).…”
Section: Resultsmentioning
confidence: 99%
“…Apparently, most cells, whether mammalian cells, yeasts cells, or gram-positive or gram-negative bacteria, can hydrolyze FDA or cFDA (2,5,21,24). A number of studies on the esterase activity of yeast cells (10,17,18,31,33), which indicated that several different activities are present in S. cerevisiae, have been carried out. However, generally, p-nitrophenyl acetate or naphthyl acetates were used as esterase substrates, and there is no available information about FDA or cFDA conversion by intracellular esterases in yeast cells.…”
mentioning
confidence: 99%